04 KONTRIBUSI PRODUKSI PADI SAWAH DAERAH SENTRA SIPILU (Sidrap, Pinrang, Luwu ) TERHADAP PRODUKSI PADI SAWAH DI SULAWESI SELATAN - Jurnal Agribis; Jusnawati Jusnawati; Arifin Arifin; Abd. Asis Pata (Jurnal Agribis, 2020)
This research was conducted in the SIPILU Center area (Sidrap, Pinrang, Luwu), South Sulawesi Province. This location was chosen because it is one of the areas that has rice production, which is scattered in an area known as a rice granary area. The data used is quantitative data is a type of data that can be measured (measurable) or calculated directly as numerical or numeric variables, and secondary data is data that is already contained in literature or official data. The type of data used in this research is time series data. The objectives of this study were: To determine lowland rice production in the SIPILU center area in South Sulawesi. Data were collected from the results of researching at the Maros Central Bureau of Statistics. The collected data is then tabulated to obtain real data used for production contribution purposes. This study uses a method of analyzing the contribution of lowland rice production in central areas to rice production in South Sulawesi divided by the total production of South Sulawesi rice multiplied by one hundred percent. The results showed that the Contribution of Paddy Paddy Production in Sentra Sipilu Area was 14,136,031.31 and South Sulawesi as much as 55,041,131.00 tons.